Secure coding in software development - Zainuddin @ Zenah, Nor Harisah; Abdul Aziz, Normaziah (2011)
The demand of secure computing systems and its platform is crucial in today's networked and computing world. As the number of illegitimate users and applications increased, the systems vulnerabilities can be a treat to individuals and organizations. This paper highlights software vulnerabilities and approaches to address them. In addition to such awareness that has been going on for the past decade, this research proposed a tool that can increase engineer's skills and knowledge towards secure software in building secure system. This proposed tool will be discussed about the software vulnerabilities and present these vulnerabilities in the form of exercises, questions, queries, and solution for the users including some examples for every vulnerability in order to give more clearer understanding to the users.